Pharmacogenetics of human sulfotransferases and impact of amino acid exchange on Phase II drug metabolism. Issue 11 (November 2022) - Isvoran, Adriana; Peng, Yunhui; Ceauranu, Silvana; Schmidt, Leon; Nicot, Arnaud B; Miteva, Maria A
Highlight: Sulfotransferases (SULTs) sulfate many endogenous compounds and a variety of xenobiotics and drugs. The interindividual variability of SULTs and its impact on phase II drug metabolism are reviewed. Structural bases of amino-acid variants and molecular mechanisms affecting drug metabolism are discussed. Structural analyses of key alloforms of SULT1A1 are presented. Abstract : Sulfotransferases (SULTs) are Phase II drug-metabolizing enzymes (DMEs) catalyzing the sulfation of a variety of endogenous compounds, natural products, and drugs. Various drugs, such as nonsteroidal anti-inflammatory drugs (NSAIDS) can inhibit SULTs, affecting drug–drug interactions. Several polymorphisms have been identified for SULTs that might be crucial for interindividual variability in drug response and toxicity or for increased disease risk. Here, we review current knowledge on non-synonymous single nucleotide polymorphisms (nsSNPs) of human SULTs, focusing on the coded SULT allozymes and molecular mechanisms explaining their variable activity, which is essential for personalized medicine. We discuss the structural and dynamic bases of key amino acid (AA) variants implicated in the impacts on drug metabolism in the case of SULT1A1, as revealed by molecular modeling approaches.